The Theban Parthenon: Contextualising Female Lay Spirituality in a Twelfth-Century Byzantine Provincial City - Wu, Gang (The journal of ecclesiastical history, 2026)
Stemming from a canonical commentary of Theodore Balsamon (1130s-1195), this article examines an underexplored Byzantine Christian practice: the consecration of virgins. It focuses on an unusual religious establishment, a parthenon, founded in Thebes by its metropolitan John Kaloktenes (1166-c.1190), which accommodated lay virgins to pursue asceticism without demonstrating monastic commitments. It investigates the practice's origins, development and significance in Byzantine religious heritage, highlighting Kaloktenes's innovative revival of the practice. This study offers a unique case for exploring Byzantine monasticism and ecclesiastical leadership, while also demonstrating the potential for integrating Byzantium into the religious movements of the contemporary Latin West.